A community hub approach to older people's housing. (13th March 2017) - Evans, Simon; Atkinson, Teresa; Darton, Robin; Cameron, Ailsa; Netten, Ann; Smith, Randall; Porteus, Jeremy
Abstract : Purpose: The purpose of this paper is to explore the potential of housing with care schemes to act as community hubs. The analysis highlights a range of benefits, barriers and facilitators. Design/methodology/approach: Data are presented from the Adult Social Services Environments and Settings project which used a mixed methods approach including a review of the literature, surveys and in-depth case study interviews. Findings: Most housing with care schemes have a restaurant or café, communal lounge, garden, hairdresser, activity room and laundrette, while many also have a library, gym, computer access and a shop. Many of these facilities are open not just to residents but also to the wider community, reflecting a more integrated approach to community health and adult social care, by sharing access to primary health care and social services between people living in the scheme and those living nearby. Potential benefits of this approach include the integration of older people's housing, reduced isolation and increased cost effectiveness of local services through economies of scale and by maximising preventative approaches to health and wellbeing. Successful implementation of the model depends on a range of criteria including being located within or close to a residential area and having on-site facilities that are accessible to the public. Originality/value: This paper is part of a very new literature on community hub models of housing with care in the UK. In the light of new requirements under the Care Act to better coordinate community services, it provides insights into how this approach can work and offers an analysis of the benefits and challenges that will be of interest to commissioners and providers as well as planners. This was a small scale research project based on four case studies. Caution should be taken when considering the findings in different settings.